Pengaruh ownership structure dan board composition terhadap kebijakan dividen pada perusahaan manufaktur di Bursa Efek Indonesia periode 2019-2023 - Ganesti , Dewi Ayu Kartika (Jurnal Ilmu Manajemen, 2025)
This study aims to analyze the influence of ownership structure and board composition  on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange during the period 2019-2023. Ownership structure in this study involves three variables that are used as measurement aspects, namely family ownership, state ownership , and foreign ownership. Meanwhile, board composition  is measured using two aspects, namely board gender diversity and board independence. Previous years' dividends and profitability serve as control variables to strengthen the regression model. The data in this study is quantitative and sourced from secondary data. The population in this study involves manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2023. Based on the results of purposive sampling as the sampling technique, 64 companies were selected as the research sample.  The analysis was conducted using the logistic regression method through SPSS version 2025. The results showed that simultaneously, the variables of family ownership, state ownership , foreign ownership, board gender diversity, and board independence affected dividend policy. Meanwhile, based on  the results of the partial influence test, it was found that there was no influence between family ownership, state ownership , foreign ownership, board gender diversity, and board independence on dividend policy